A systematic review of local antibiotic devices used to improve wound healing following the surgical management of foot infections in diabetics. (November 2018) - Marson, B. A.; Deshmukh, S. R.; Grindlay, D. J. C.; Ollivere, B. J.; Scammell, B. E.
Abstract : Aims: Local antibiotics are used in the surgical management of foot infection in diabetic patients. This systematic review analyzes the available evidence of the use of local antibiotic delivery systems as an adjunct to surgery. Materials and Methods: Databases were searched to identify eligible studies and 13 were identified for inclusion. Results: Overall, the quality of the studies was poor. A single trial suggested that wound healing is quicker when a gentamicin-impregnated collagen sponge was implanted at time of surgery, with no difference in length of stay or rate of amputation. Results from studies with high risk of bias indicated no change in wound healing when a gentamicin-impregnated sponge was implanted during transmetatarsal amputation, but a reduction in the incidence of wound breakdown (8% vs 25%, not statistically significant) was identified. A significant cost reduction was identified when using an antimicrobial gel to deliver antibiotics and anti-biofilm agents (quorum-sensing inhibitors) compared with routine dressings and systemic antibiotics. Analyses of case series identified 485 patients who were treated using local antibiotic delivery devices. The rates of wound healing, re-operation, and mortality were comparable to those that have been previously reported for the routine management of these infections. Conclusion: There is a lack of good-quality evidence to support the use of local antibiotic delivery devices in the treatment of foot infections in patients with diabetes. Cite this article: Bone Joint J 2018;100-B:1409–15.